(3TQM gOGjI GdMceIs - (3GdMSjfj GdnerjnHPj, bGVj ejQ, MSjf Hf eYjf GdOjf, J (B910 (3g`s
(3ChdgG (B:s
... (3ef GdYdeGA hMe ZajQ ef GdMceGA CqHO Gddg LdGdge hNdO XdGdge hQSeJ aj CjGe GdJMUjd Ydi CcKQ cJHgG CQbGeG cUjQI JYO ddfGXQjf ajg HUjQI hajg GdgOGjI (B...s
(3BNQgG (B:s
... (3Ef GdhGLH Ydi WGdH GdMb eWGdYI cJH GdTjNjf CHj Ydj hTgGH GdOjf GdebJhd bOS SQgeG hahb WhQgeG WhQ ZjQ bOQg GdcHQjJ GdCMeQ hJhajb GdhUhd Edjg ef Gddg GdCcHQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\260s
(3cTa GdXfhf (B2\2029s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs